Kajian Yuridis Tentang Perjanjian Kerja Waktu Tertentu Pada PT. Kiara Beautymed Di Kabupaten Bantul - Nur Aisyiah, Dian; Purwono, R. Triyuli; R. Triyuli Purwono (Faculty of Law, University of Mataram, 2024)
Law Number 13 of 2003 concerning Employment is a milestone in the protection of workers in Indonesia. The hypothesis of this research is that there are companies that still make fixed-term work agreements (PKWT) that do not pay attention to existing regulations and the interests of workers. The purpose of companies using PKWT is market demands which require a fast process in improving company services. This research aims to determine the suitability of implementing a fixed-term work agreement at PT. Kiara BeautyMed is in accordance with the applicable regulations of Law Number 13 of 2003 concerning Employment, as well as to identify obstacles in implementing PKWT at PT. Kiara BeautyMed and how to solve it. This research uses an Empirical Juridical approach method. The specifications used are descriptive, the data sources used are primary data and secondary data. The analysis used is qualitative analysis. The research location was carried out at PT. Kiara BeautyMed. Based on this research, the results showed that PT Kiara BeautyMed as the first party and second party workers had implemented a certain time work agreement properly and in accordance with the provisions of the applicable laws. This suitability is proven by the absence of a trial work period for contract workers. This is in accordance with article 58 paragraphs 1 and 2 of Law no. 13 of 2003 concerning Employment obstacles that occur at PT Kiara BeautyMed in the form of administrative problem.